2017
DOI: 10.1128/jvi.02253-16
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Glycine Residue Is Required for Proper Functioning of a Baculovirus VP39 Protein

Abstract: The baculovirus VP39 protein is a major nucleocapsid protein essential for viral propagation. However, the critical domains or residues of the VP39 protein have not yet been identified. Here, we performed mutagenesis experiments with Bombyx mori nucleopolyhedrovirus (BmNPV) using 5-bromo-2=-deoxyuridine and isolated a BmNPV mutant that produced fewer occlusion bodies than the wild-type virus. This mutant also produced fewer infectious budded viruses (BVs) than the wildtype virus in both cultured cells and B. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Our observations indicate that, in cells infected with the AC102-K66A mutant, expression of the very late protein polyhedrin is also delayed and reduced, and fewer infected cells contain polyhedra compared to WOBpos-infected cells. This phenotype is similar to that recently observed for a virus carrying a point mutation in VP39 (VP39-G276S), which exhibits reduced expression of polyhedrin and fewer polyhedra (37). It was suggested that lower polyhedrin expression in the VP39-G276S mutant might result from the sequestration of viral DNA in aberrant tubular nucleocapsid-like structures, reducing transcription of viral genes, and a similar phenomenon may account for the phenotype of the AC102-K66A mutant.…”
Section: Discussionsupporting
confidence: 84%
“…Our observations indicate that, in cells infected with the AC102-K66A mutant, expression of the very late protein polyhedrin is also delayed and reduced, and fewer infected cells contain polyhedra compared to WOBpos-infected cells. This phenotype is similar to that recently observed for a virus carrying a point mutation in VP39 (VP39-G276S), which exhibits reduced expression of polyhedrin and fewer polyhedra (37). It was suggested that lower polyhedrin expression in the VP39-G276S mutant might result from the sequestration of viral DNA in aberrant tubular nucleocapsid-like structures, reducing transcription of viral genes, and a similar phenomenon may account for the phenotype of the AC102-K66A mutant.…”
Section: Discussionsupporting
confidence: 84%
“…Our observations indicate that, in cells infected with the AC102-K66A mutant, expression of the very late protein polyhedrin is also delayed and reduced, and fewer infected cells contain polyhedra as compared with WOBpos-infected cells. This phenotype is similar to that recently observed for a virus carrying a point mutation in VP39 (VP39-G276S), which exhibits reduced expression of polyhedrin and fewer polyhedra (36). It was suggested that lower polyhedrin expression in the VP39-G276S mutant might result from the sequestration of viral DNA in aberrant tubular nucleocapsid-like structures, and a similar phenomenon may account for the phenotype of the AC102-K66A mutant.…”
Section: Discussionsupporting
confidence: 87%
“…In LQ-R, leucine and glutamine account for 14.9% and 12.8%, respectively. In another nucleocapsid protein VP39 of baculovirus, it is known that amino acid substitution at glycine 276 affects nucleocapsid assembly and that this residue is completely conserved among various baculovirus families [ 11 ], suggesting that certain glycine residues are essential for proper function of the nucleocapsid protein. Even though N CoV2 contains 43 glycines in total, which account for 10.3% of 419 residues, there have not been systematic studies on the role of glycine and thus the possible roles of glycine in the N CoV2 function remain unclear.…”
Section: Sars-cov-2 Nucleocapsid Proteinmentioning
confidence: 99%